Bilateral syndactyly of both extremities in a new born - a case report - N Ratnakar Rao; N Bhavani (Wolters Kluwer Medknow Publications, 2012)
Syndactyly is a condition where in two or more digits are fused together. A newborn female baby showed not only webbing of the fingers but also toes. X-ray of both hands and feet showed no bony fusion. Syndactyly is a rare anomaly that has surgical and psychological implications. Normally mesenchyme between prospective digits in hand and foot plates is removed by cell death (apoptosis) when this process fails the result is fusion between two or more digits. It occurs as one in every 2000 to 2500 births and twice as common in males. Though it is very rare it can be corrected surgically and child can live a normal life. The knowledge of digit formation and causes for abnormalities in the digits and toes are important for radiologists, obstetricians and surgeons for accurate diagnostic interpretation.